(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2019)
Introduction. The study of physical properties of substances using pulsed electromagnetic radiation has become widespread in optical and radio wave spectroscopy. Pulsed Fourier spectroscopy of nuclear quadruple resonance (NQR) is based on powerful radio frequency excitation pulses and the use of highly sensitive equipment. In response to the short broadband δ-pulse, this method ensures the excitation of all resonance frequencies of the NQR spectrum. The method of detecting free induction decay signals (FID) requires a thorough analysis, since its implementation governs the accuracy of visualization of complex resonance spectra, especially when it comes to multi-pulse experiments. Recently, in the developed countries of the world, much work is in progress on the development of radiotechnical systems that are referred to collectively as Software Defined Radio (SDR). The choice of NQR detecting methods. It is known that in the pulsed NQR, the FID signals are detected by transferring the resonance spectrum to the low frequency (LF) range by subtracting the reference frequency, which is close to the frequency of the resonating nucleus. The features of the Fourier transform create additional problems when selecting the reference frequency for the synchronous detector. Another option is to apply a quadrature detection of FID which allows an increase in the signal-to-noise ratio by a factor of square root. Apart from increasing sensitivity, the use of quadrature detection imposes some restrictions. In reality there are small residual signals - quadrature reflections in the spectra. Simulation modeling of the receive path of radiospectrometer developed on the principle of direct digitization of a signal. The structure and MATLAB Simulink model of a digital quadrature receiver of nuclear quadruple resonance signals were developed. The synthesis of compensating filters and computer simulation of signal transformations in the receive path of radiospectrometer were performed. It was established that the application of the principle of direct digitization of the free induction decay signal made it possible to significantly reduce the length of the analog portion of the receiver, and, consequently, reduce the noise of the useful signal and the level of out-of-band higher order spectral components. In particular, with a sampling frequency of 17 MHz and a cutoff frequency of the compensating LPF of 1 MHz, the level of side and out-of-band emissions in the effective bandwidth of the SDR is not more than -100 dB. Algorithm of phase cycles CYCLOPS. An algorithm based on the principle of four-phase cycles CYCLOPS is integrated into the SDR receiver simulation model, which ensures the reduction of quadrature reflections to 1 %. The concept of proposed model realization on the basis of DSP libraries System Toolbox and FDATool makes possible its efficient implementation on the basis of field-programmable gate arrays. In this case, the FPGA of Intel (Altera) or Xilinx are effective, since CAD systems of their configuration structures are closely integrated with MATLAB.